2021
DOI: 10.1155/2021/5795884
|View full text |Cite
|
Sign up to set email alerts
|

Student Physical Health Information Management Model under Big Data Environment

Abstract: Health is considered an important foundation for students’ success. However, with the accelerated pace of life, rising pressure from various parties, weak health awareness, lack of exercise time, and other reasons, students’ physical quality is generally declining, the incidence of health diseases is increasing, and the onset age tends to be younger. With the development of the concept of “health first,” health management continues to expand and extend and students’ health management has attracted more attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Seasonal effects are another example of environmental barriers. Reluctance to participate in sports or sports activities because of the weather is one example [ 12 ]. In China, most scholars assess students' physical health based on three factors: body shape, physical function, and physical quality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal effects are another example of environmental barriers. Reluctance to participate in sports or sports activities because of the weather is one example [ 12 ]. In China, most scholars assess students' physical health based on three factors: body shape, physical function, and physical quality.…”
Section: Methodsmentioning
confidence: 99%
“…Wang et al conducted a two-semester experiment on 286 students who used the running APP in Normal University. Through the comparison of physical fitness test results, they found that the students' height did not change much, and insisting on physical exercise would improve their vital capacity to a certain extent [ 12 ]. Yang et al used the experimental control method to investigate the influence of mobile APP fitness software on college students' physical fitness level.…”
Section: Related Workmentioning
confidence: 99%
“…In order to make students' health management more scientific, standardized, and effective, Wang H put forward big data technology to build student health information management model. He combined the data collection, supervision, data analysis, and data application of students' health and gradually improved the National Students' health monitoring and evaluation system [1]. In view of the constraints of simultaneous shortage and idleness of students' physical exercise and gymnasium facilities, Wang proposed a gymnasium operation and management mode based on College Students' behavior model for the purpose to inspire the innovation of university gymnasium management mode [2].…”
Section: Related Workmentioning
confidence: 99%
“…Kaviyarasi uses data mining and other technologies to obtain college student information, and formulates corresponding college student management plans based on college student information ( Kaviyarasi and Balasubramanian, 2018 ). Wang’s research pointed out that the student management model that obtained student information with big data and constructed can manage college students well ( Wang et al, 2021 ). Wang builds a management model for college students’ sports problems, which can effectively manage the sports aspects of college students ( Wang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%